2008
DOI: 10.1128/iai.00168-08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mating Type, Serotype, and Ploidy on the Virulence of Cryptococcus neoformans

Abstract: Hybridization with polyploidization is a significant biological force driving evolution. The effect of combining two distinct genomes in one organism on the virulence potential of pathogenic fungi is not clear. Cryptococcus neoformans, the most common cause of fungal infection of the central nervous system, has a bipolar mating system with a and ␣ mating types and occurs as A (haploid), D (haploid), and AD hybrid (mostly diploid) serotypes. Diploid AD hybrids are derived either from a-␣ mating or from unisexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
91
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 82 publications
3
91
1
6
Order By: Relevance
“…However, other studies suggest that ␣ isolates in general are more virulent than a strains (12,126,145). Recently, Lin et al (151) carried out a detailed analysis to investigate the effect of ploidy and mating type on virulence of serotype A and serotype AD isolates. Somewhat surprisingly, they found that diploid isolates are slightly less virulent than haploid isolates in a murine inhalation model.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies suggest that ␣ isolates in general are more virulent than a strains (12,126,145). Recently, Lin et al (151) carried out a detailed analysis to investigate the effect of ploidy and mating type on virulence of serotype A and serotype AD isolates. Somewhat surprisingly, they found that diploid isolates are slightly less virulent than haploid isolates in a murine inhalation model.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…They are also primary pathogens and a cause of pulmonary disease (201). The majority of clinical isolates (up to 95% of human infections) are serotype A, which are also more virulent in animal models (151).…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…Phenotypic assays were performed as described previously (37). Briefly, strains to be tested were grown overnight in YPD liquid medium.…”
Section: Figmentioning
confidence: 99%
“…The in vitro phenotypic assays were performed as previously described (31,35). Briefly, yeast cells were grown on YPD medium overnight and washed three times with water.…”
Section: Figmentioning
confidence: 99%
“…1), also exhibit low levels of virulence in an intravenous infection model of murine cryptococcosis (33). Studying cryptococcal virulence with these serotype D congenic pairs often requires long study periods (40 to ϳϾ100 days), unnatural intravenous inoculation, and relatively high infection doses (1 ϫ 10 6 to ϳ1 ϫ 10 7 cells/mouse) (27,(32)(33)(34)(35). The construction of the H99 congenic pair strains (KN99␣/ KN99a) facilitated genetic analyses in the serotype A background.…”
mentioning
confidence: 99%